Erythrocyte phospho-signalling is dynamically altered during infection with Plasmodium falciparum - Jack D. Adderley; Christian Doerig (Microbial Cell, 2020)
It is well established that intracellular pathogens mobilise signalling pathways to manipulate gene expression of their host cell to promote their own survival. Surprisingly, there is evidence that specific host signalling molecules are likewise activated in a-nucleated erythrocytes in response to infection with malaria parasites. In this paper (Adderley et al., Nature Communications 2020), we report the system-wide assessment of host erythrocyte signalling during the course of infection with Plasmodium falciparum. This was achieved through the use of antibody microarrays containing >800 antibodies directed against human signalling proteins, which enabled us to interrogate the status of host erythrocyte signalling pathways at the ring, trophozoite and schizont stages of parasite development. This not only confirmed the pre-existing fragmentary data on the activation of a host erythrocyte PAK-MEK pathway, but also identified dynamic changes to many additional signalling elements, with trophozoite-infected erythrocytes displaying the largest mobilisation of host cell signalling. This study generated a comprehensive dataset on the modulation of host erythrocyte signalling during infection with P. falciparum, and provides the proof of principle that human protein kinases activated by Plasmodium infection represent attractive targets for antimalarial intervention.